2018
DOI: 10.1210/en.2018-00064
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Tissue Mass Spectrometry Imaging Reveals a Refined Functional Anatomy of the Human Adult Adrenal Gland

Abstract: In the adrenal gland, neuroendocrine cells that synthesize catecholamines and epithelial cells that produce steroid hormones are united beneath a common organ capsule to function as a single stress-responsive organ. The functional anatomy of the steroid hormone-producing adrenal cortex and the catecholamine-producing medulla is ill defined at the level of small molecules. Here, we report a comprehensive high-resolution mass spectrometry imaging (MSI) map of the normal human adrenal gland. A large variety of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 65 publications
1
37
0
Order By: Relevance
“…In addition to the intensities of mass spectrometry, MSI studies by high-resolution matrix-assisted laser desorption/ionization-Fourier transform-ion cyclotron resonance (MALDI-FT-ICR) permit correlations with the spatial information conveyed by conventional histology. This technique has recently allowed us to refine the functional anatomy of the human adrenal gland, which supports the usefulness of these analyses for steroid-producing tissues also (17).…”
Section: Introductionmentioning
confidence: 59%
“…In addition to the intensities of mass spectrometry, MSI studies by high-resolution matrix-assisted laser desorption/ionization-Fourier transform-ion cyclotron resonance (MALDI-FT-ICR) permit correlations with the spatial information conveyed by conventional histology. This technique has recently allowed us to refine the functional anatomy of the human adrenal gland, which supports the usefulness of these analyses for steroid-producing tissues also (17).…”
Section: Introductionmentioning
confidence: 59%
“…The application of MALDI-MSI to adrenal tissue sections allowed quantification of many small molecules across the tissue section at the same time [53]. Sun et al showed that high resolution MALDI-MSI in conjunction to adrenal steroidogenic enzyme IHC could correlate metabolites and their associated metabolic pathways with the functional zonation of the normal adrenal gland [54]. Recently, Murakami et al extended these studies to KCNJ5 and CACNA1D-mutated APA using MALDI-MSI and found a relationship between higher 18-oxocortisol levels, lower intensity of CYP11B1 staining and a higher possibility of postoperative biochemical cure for PA [55].…”
Section: Molecular Characterization Of Apccmentioning
confidence: 99%
“…We illustrated how METASPACE facilitates metabolite annotation for imaging MS, reveals the state of the art of the imaging MS technology, enables large-scale analysis of spatial metabolomes, and supports drug development. METASPACE, although not yet published, was already used in several publications [37][38][39][40][41][42][43] and highlighted in numerous reviews that indicates the significance and uniqueness of this resource for the imaging MS field. With the current rate of growth of 1000 datasets a year, its molecular and biological coverage will soon increase enough to provide spatial metabolomics atlases for various tissues, organs, and organisms.…”
Section: Discussionmentioning
confidence: 99%